DISCOVER ISLAMIC WORK ETHICS FACTORS FOR SHAPING WORK CULTURE IN INDONESIA - Faizah, Siti Inayatul; Widiastuti, Tika; Marijan, Kacung; Dewi, Eka Puspa; Baihaqi, Muhammad Nadif (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2024)
Introduction: : The fundamental theory posits that Islamic values encompass all human activities, including work ethics as an essential component of organizational behavior. However, today’s society is facing a decline in work ethics, necessitating readjustment. This study aims to bridge the gap by examining prior research on Islamic work ethics in Indonesia. Methods: A systematic literature review method was used to delve deeper into the development of research topics over the past decade (2014-2023) through a search of Scopus-indexed articles. After a screening process, the final sample, consisting of 38 articles, was processed for further analysis using meta synthesis approach to explore more specific understanding of Islamic work ethics by using Nvivo software. Results: The results showed that Islamic work ethics were affected by three main factors: community patterns, role of Islam, and organizational concept. The relationship between these three factors can encourage positive behavior in the workplace in Indonesia. Conclusion and suggestion: Islamic work ethics in Indonesia are not limited to religious value, but also the culture of the community. Mapping ideas of the three categories of Islamic work ethics in Indonesia can be useful for future empirical research to analyze the relationship among factors in shaping Islamic work ethics in Indonesia. The mapping ideas could also be implemented by organizations in daily business practices.